2017
DOI: 10.3363/prb.33.14
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of millimeter-scale fibrous octacalcium phosphate particles by homogeneous precipitation method

Abstract: Preparation conditions of millimeter-scale fibrous octacalcium phosphate (Ca8H2(PO4)6·5H2O: OCP) particles by homogeneous precipitation method were examined, using Ca(NO3)2, (NH4)2HPO4, urea ((NH2)2CO; precipitant) and conc. HNO3 (precipitation inhibitor). The starting solution (200 cm 3 ) with 0.0266 mol•dm -3 Ca(NO3)2 and 0.0200 mol•dm -3 (NH4)2HPO4, i.e., the stoichiometric Ca/P ratio of OCP (=1.33), was heated under reflux at 80ºC for 24 h in order to encourage the precipitation, due to the hydrolysis of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In contrast, fibrous precipitates were formed in the SBF modified with ALP ( Figure 3(d) ), although the changes in the Ca and P concentrations, and the pH of the SBF with the sample soaking period were almost the same, regardless of the presence of ALP ( Figures 5 and 6 ). Fibrous-shaped HAp and OCP were reported previously [ 49 , 50 ]; therefore, these precipitates are likely to be HAp and/or OCP, although these crystalline phases could not be detected by XRD because their amount was lower than the detection limit ( Figure 4(d) ). Based on the SEM observation that the morphology of the precipitates was different in the presence and absence of ALP ( Figure 3(d) ), ALP likely had an effect on the formation of precipitates in the ALP-modified SBF soaked with CaDoP.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, fibrous precipitates were formed in the SBF modified with ALP ( Figure 3(d) ), although the changes in the Ca and P concentrations, and the pH of the SBF with the sample soaking period were almost the same, regardless of the presence of ALP ( Figures 5 and 6 ). Fibrous-shaped HAp and OCP were reported previously [ 49 , 50 ]; therefore, these precipitates are likely to be HAp and/or OCP, although these crystalline phases could not be detected by XRD because their amount was lower than the detection limit ( Figure 4(d) ). Based on the SEM observation that the morphology of the precipitates was different in the presence and absence of ALP ( Figure 3(d) ), ALP likely had an effect on the formation of precipitates in the ALP-modified SBF soaked with CaDoP.…”
Section: Discussionmentioning
confidence: 76%
“…OCP was reported to precipitate as 3D ower-like particles consisting of belt, 29,30,53 plate 27,54 and ber. 34,55,56 It was reported that such organic molecules as cetyltrimethylammonium bromide (CTAB) 57 and ameloginin 58 played a role to control the particle size of OCP. Belt-shaped particle of OCP with the size of 1-3 mm was obtained by the precipitation in the presence of CTAB.…”
Section: Discussionmentioning
confidence: 99%
“…The present authors also took notice of the preparation of TiO2 nanoparticles from the aqueous solution, with the prospects of the fabrication of composite materials with other functional materials in order to achieve the one-pot liquid phase synthesis. We further focused on the preparation of TiO2 nanoparticles through the homogeneous precipitation method using urea, because our previous reports [7][8] demonstrated that the homogeneous precipitation method has a special and simple technique to control the amount of the reaction-participating ligands from the urea, due to the slow hydrolysis to release ammonia in the solution. In order to meet such requirement, we selected a potassium titanium oxalate (K2TiO(C2O4)2) having the characteristic crystal structure of 'eightmembered rings of four Ti and four O atoms' as a starting material; each Ti 4+ ion having the six ligand sites forms the distorted octahedron, two of which are the μ-oxo bridging oxygen ions belonging to the eight-membered ring and four of which are occupied by two chelate-coupled oxalate groups.…”
Section: Introductionmentioning
confidence: 99%